Students’ Perception toward the Use of Moodle-Reader for Improving Reading Comprehension - Ivo Riyani; Regina Regina; Wardah Wardah (FKIP - Universitas Tanjungpura, 2023)
This research aimed to investigate the students’ perception toward the use of Moodle-reader for improving reading comprehension. This study was descriptive research with a qualitative approach that used questionnaires and interviews. The respondents were 20 participants who were part of the member of Academic Resources Center (ARC) as students in the English Education Student Program at Universitas Tanjungpura. The researcher found that the perceptions of each student about using Moodle-reader for improvement could be the same and also different. It depends on the student’s perspective or thoughts, feelings, and beliefs. Overall, the students responded positively about the use of Moodle-reader for improving reading comprehension. The researcher concluded that the students agreed that Moodle-reader is suitable for independent learning and improving reading comprehension. The researcher found that the five aspects (ease of access to Moodle-reader, perceived usefulness in Moodle-reader, students’ motivation using Moodle-reader, students’ satisfaction, and the features in Moodle reader) can influence students reading comprehension. Moodle-reader provided varieties of books based on students’ levels. Students could be enjoying the books. It makes students motivated to read many books. Therefore, Moodle-reader could positively impact students and improve their reading ability, especially in reading comprehension.